Non-Newtonian Behavior Effect on Gas-liquid Mass Transfer using an Anchor Impeller for CSTR Bioreactors: A CFD Approach (2018)
ABSTRACT: Objectives: kLa mass transfer coefficient was predicted using CFD (computational fluid dynamics) for analyzing non-newtonian effects on gas liquid mass transfer in a 10 L bioreactor stirred with an Anchor Impeller. Methods/Statistical Analysis: The set up bioreactor configurations were defined by typical culturing conditions used for fungi organism. Bubble breakage frequency and coalescence rate were simulated using Luo - Colaloglou and Tavlarides models and PBM approaches, respectively. Simulated results from different shear rates due to non-newtonian behaviour are compared by analyzing its influences in bubble size and power input. Findings: A clear relationship between high levels of shear rates and small bubble sizes is found in this work. The later is also associated with the high values of kLa simulated (270 h-1) and compared to levels found at low shear rates (62 h-1). Application/Improvements: Impressed by these findings new design optimizations for non-newtonian bioprocessing applications would be improved using CFD.